Understanding factors affecting participation rates and facilitators of compliance in breast screening programme in the UK: A cross-sectional mixed methods study - Holly West; Victor Chigbundu Nwaiwu; Sherril Spencer (Evidence Synthesis in Healthcare Connect, 2026)
Globally, breast cancer remains the most diagnosed cancer in women, with evidence showing that the participation rates of the National Health Service (NHS) breast screening program continue to fall below the national target. This study investigates factors influencing participation rates and facilitators of compliance. A cross-sectional, mixed-methods study involving 73 eligible women aged 50-70, living in the UK. Results show that most participants (97%) regularly attended screening appointments when invited, and four main factors influenced participation: positive experiences and regular attendance, importance of early detection and family history, fear and anxiety, and accessibility and convenience. Facilitators of compliance included easy and flexible scheduling, convenient locations with parking spaces, a friendly and professional health screening team, a positive first-time experience, and health-related motivations. Reflecting the evolving landscape of the UK, the most notable issue is the lack of ethnic diversity among study participants. Future interventions should address this shift, moving away from generic invitations toward personalized, culturally tailored, data-driven approaches.